In Silico Approaches to Study the Anti Cancer Potential of Bioactive Compounds of Apium leptophyllum Pers by Molecular Docking: Life Sciences-Biochemistry for Better Diagnosis and Therapy - M.Siva Ganesh; Dr. J.Radhika (International Journal of Life Science and Pharma Research, 2022)
The Indian traditional health care system has suggested the presence of bioactive compounds in herbs used for the treatment of cancer. Natural medicinal plants have been used as therapeutics since the Vedic era. In-Silico studies have demonstrated to be an important tool that facilitates the use of the structural diversity of the natural products and designing new drugs for various diseases. Isolation studies by GC-MS analysis revealed that the ethanolic seed extract of Apium leptophyllum Pers contain natural bioactive compounds such as Thymol, Alpha –Terpineol and 9,12- Octadecadienoyl chloride(Z-Z-). These three active compounds are found in higher concentration in the ethanolic extract of Apium leptophyllum Pers seeds. The isolated active compounds were subjected to docking studies using Glide module (Schrodinger). Research was performed to find out the potential molecular targets for these selected compounds. The effectiveness of In-silico approach was carried out by performing docking of known specific phenolic mono terpenoids such as Thymol inhibitors against their respective selected macromolecules of cancer cell receptor. The present study was carried out to identify potential inhibitors for Bruton’s tyrosine kinase and checkpoint kinase 2. The docking studies revealed that the some essential active compounds such as Thymol, Alpha -Terpineol, and 9, 12- Octadecadienoyl chloride(Z-Z-) isolated by GC-MS analysis have potent anticancer activity against cancer cell. The study will further pave the way in designing other potent drugs and drug analogs. The novel molecular entities have the potential as leads which certainly aid in designing anti-cancer molecules in short span of time.